A novel peptide for efficient siRNA delivery in vitro and therapeutics in vivo. (15th July 2015) - Pan, Ran; Xu, Wen; Yuan, Feng; Chu, Dafeng; Ding, Yong; Chen, Baoling; Jafari, Mousa; Yuan, Yongfang; Chen, P.
Graphical abstract: Abstract: Small interfering RNA (siRNA) shows great therapeutic potential due to its ability to regulate gene expression in a highly selective manner. However, its application has been limited by ineffective cellular uptake of siRNAs. To achieve successful gene-silencing efficiency, a safe and effective delivery vector is generally required. In this study, we designed a series of amphipathic peptides that comprised a variant of a nuclear localization sequence, 0–6 histidine residues and an optional stearic acid group. Among these candidates, STR-HK exhibited good characteristics as a safe and efficient siRNA delivery vector, facilitating efficient siRNA delivery to mammalian cells without causing cytotoxicity. Moreover, the intratumoral injection of STR-HK/siRNA complexes achieved high anti-tumor activity through the downregulation of the Bcl-2 protein in mice, with an inhibition rate of 62.8%. Our data demonstrate that STR-HK is a highly promising siRNA delivery vector for therapeutic applications.